Recent Advances in MercuryDPM - Thornton, Anthony R.; Plath, Timo; Ostanin, Igor; Götz, Holger; Bisschop, Jan-Willem; Hassan, Mohamed; Roeplal, Raïsa; Wang, Xiuqi; Pourandi, Sahar; Weinhart, Thomas (Mathematics in Computer Science, 2023)
In this paper we introduce the open-source code MercuryDPM: a code for simulating discrete particles. The paper discusses software and management issues that may be interesting for the developers of other open-source codes. Then we review the new features that have been added since the last publication: an improved Hertz-Mindlin model; a new liquid bridge model of Lian and Seville; a droplet-spray model; better support for re-creating complex, measured particle size distributions; a new implementation of rigid clumps; an implementation of elastic membranes; a wear model for walls; a soft-kill feature and a cloud-deployment interface for AWS.
CRIS-Team Scopus Importer:2023-06-30
Keywords: (Wet) Granular Materials; Cloud compung; DEM; DPM; MercuryDPM; open-source